A Comparative study of osteoarthritic knee patients between urban and rural areas in knee severity and quality of life - Areerat Siripongpan; Bura Sindhupakorn (Health Psychology Research)
Osteoarthritis Knee (OA) is the leading cause of pain and disability. This may affect the patient's quality of life (QoL) and lead to the onset of mental disorders. The aim of this study was 1) To find the correlation between the severity of OA, depression, and QoL. 2) To compare the severity of OA knee and QoL between urban and rural areas. 199 patients were diagnosed with OA. All patients had self-assessment with questionnaires in terms of 1) demographic data, 2) the knee severity by using Oxford Knee Score, 3) Depression screening by using Patient Health Questionnaire, and 4) World Health Organization Quality of Life Brief-Thai. The results revealed that OA knee patients had excellent (no abnormal symptoms) and good (mild symptoms) levels of severity were 34.2% and 32.2%, respectively. They also had a good level of QoL. The correlation between residential area and other variables were age group (p \< 0.01), severity of osteoarthritis (p \< 0.01), and depression (p \< 0.05). The severity of OA knee and QoL in the mental health aspect was a significant difference in patients in each age group. (p \< 0.01 and p \< 0.05, respectively). Depression and QoL were not correlated. The conclusion was patients had less severity of osteoarthritis, good QoL, and no anxiety or depression. Residential areas had no impact on QoL but healthcare providers should explain the treatment plan. The next study should focus on the long term of the patient's QoL.